Telat Menikah Dalam Novel Induk Gajah Karya Ira Gita Sembiring - Putri Nabila Sulfa; Dewi Ayu Setianingsih; Yesha Tri Anita Utami; Mohamad Afrizal (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study analyzes the theme of marriage delay in the novel Induk Gajah by Ira Gita Sembiring which reflects the conflict between tradition and modernity in Indonesian society. The novel depicts social pressures, individual choices, and changes in cultural values faced by unmarried women at a certain age. The main focus of this study is to identify factors that influence the decision to postpone marriage, such as family pressures, career priorities, emotional trauma, and incompatibility with potential partners. The results of the study show that the delay in marriage, as depicted in this novel, is not a failure but a form of awareness of individual needs and rights. This novel provides a critique of societal norms that often limit women, and emphasizes the importance of freedom to choose the path of life without judgment.